Higher turnout increases incumbency advantages: Evidence from mayoral elections - Marco Frank; David Stadelmann; Benno Torgler (Economics & Politics, 2022)
We analyze the effect of electoral turnout on incumbency advantages by exploring mayoral elections in the German state of Bavaria. Mayors are elected by majority rule in two-round (runoff) elections. Between the first and second ballot of the mayoral election in March 2020, the state government announced an official state of emergency. In the second ballot, voting in person was prohibited and only postal voting was possible. To construct an instrument for electoral turnout, we use a difference-in-differences strategy by contrasting turnout in the first and second ballot in 2020 with the first and second ballots from previous elections. We use this instrument to analyze the causal effect of turnout on incumbent vote shares. A 10-percentage point increase in turnout leads to a statistically robust 3.4 percentage point higher vote share for incumbent mayors highlighting the relevance of turnout-related incumbency advantages.
Keywords: 330; incumbency effects; mayoral elections; turnout; voting in crises